Optimization of lemongrass cultivation into essential oil in Tunggularum, Wonokerto - Hidayah, Nurul; Fathurrahman , Haris Imam Karim; Fitriani , Aprilia; Sabila, Liya Yusrina (Universitas Ahmad Dahlan, 2024)
The empowerment of the community in Tunggularum, Wonokerto, aims to optimize lemongrass (Cymbopogon citratus) cultivation into essential oil products through community-based training and practical skills development. Lemongrass is widely cultivated in the area but is underutilized due to limited knowledge of its potential economic value, particularly in essential oil production. This community service project focused on addressing this gap through two primary activities: a socialization session on the essential oil distillation process and hands-on training in the operation of distillation equipment. The project involved 20–25 local participants, predominantly women, who attended both the theoretical and practical sessions. The results showed significant improvements in the participants' knowledge and skills. Over 70% of participants reported feeling more capable of managing the local lemongrass resources and demonstrated an enhanced understanding of the distillation process. The training also fostered new skills in operating distillation equipment, which further encouraged the participants to explore the business potential of lemongrass essential oil production.